The dependence of the range of fusion on some selected functions of the visual system. Part II: accommodation and dominance - Adamek, Bogdan; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
This present study is the continuation of Part I of the research into the range of fusion in which the difference between both eyeballs as far as convergent fusion is concerned was described. The phenomenon was called “visual unevenness of the range of convergent fusion”. This part of the study is devoted to the analysis of the relationship between the unevenness of the fusion, ocular dominance and accommodation. A lower range of convergent fusion was observed in the dominant eye with the higher accommodation. In contrast, a higher range of fusion was observed in the not dominant eye with lower accommodation. The authors think that the phenomenon of ocular unevenness of the range of convergent fusion does not depend on the peripheral part of visual organ. In fact, it does seem to point out to a cortical process. The authors suggest that quantitative tests on amplitude of fusion should be carried out first on the first eye and then on the other. The results obtained from both eyes should be compared with each other.